Tinjauan Politik Hukum Pidana Terhadap Kebijakan Kriminalisasi Delik Kesusilaan Dalam Undang-undang Pornografi - Wibowo, Zamhari (JURNAL ISTINBATH, 2011)
AbstrakPornography Act enactment caused controversy since it was drafted to the present. Many people argue that Pornography Act could curb freedom of expression, so that contrary to the spirit of a democratic regime. However Pornography Act is an urgent need for Indonesia since pornography has become more widespread. The penal policy may give legitimacy to the criminalization of the offenses in Pornography Act that is to protect the morality of the people of Indonesia who still uphold the oriental culture. In addition, the Pornography Act also can avoid the impact of pornography that is very dangerous, especially to the children.Keyword : Penal policy, pornography, criminalization